2011
DOI: 10.1002/gepi.20564
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype harmonization and cross-study collaboration in GWAS consortia: the GENEVA experience

Abstract: Genome-wide association study (GWAS) consortia and collaborations formed to detect genetic loci for common phenotypes or investigate gene-environment (G*E) interactions are increasingly common. While these consortia effectively increase sample size, phenotype heterogeneity across studies represents a major obstacle that limits successful identification of these associations. Investigators are faced with the challenge of how to harmonize previously collected phenotype data obtained using different data collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…However, this consideration of power has to be discussed taking into account the improved phenotypic characterisation accounting for the disease heterogeneity [30]. Large consortia on asthma genetics have been set up based on ''poor'' asthma phenotype definition, which, in the context of a highly heterogeneous disease, may explain part of the missing : p-value for the heterogeneity of the association observed between the asthma phenotypes, assessed using the multinomial model, as described in MORRIS et al [27]; + : because the GABRIEL study (MOFFATT et al [1]) includes participants from European Community Respiratory Health Survey (ECHRS), the Study on Air Pollution and Lung Disease in Adults (SAPALDIA) and the Epidemiological Study on the Genetics and Environment of Asthma (EGEA), the association from the GABRIEL study after excluding these three studies in the meta-analysis is presented.…”
Section: Discussionmentioning
confidence: 99%
“…However, this consideration of power has to be discussed taking into account the improved phenotypic characterisation accounting for the disease heterogeneity [30]. Large consortia on asthma genetics have been set up based on ''poor'' asthma phenotype definition, which, in the context of a highly heterogeneous disease, may explain part of the missing : p-value for the heterogeneity of the association observed between the asthma phenotypes, assessed using the multinomial model, as described in MORRIS et al [27]; + : because the GABRIEL study (MOFFATT et al [1]) includes participants from European Community Respiratory Health Survey (ECHRS), the Study on Air Pollution and Lung Disease in Adults (SAPALDIA) and the Epidemiological Study on the Genetics and Environment of Asthma (EGEA), the association from the GABRIEL study after excluding these three studies in the meta-analysis is presented.…”
Section: Discussionmentioning
confidence: 99%
“…These areas were targeted because we assumed that grant applications within each of these areas would study related topics, and that there would be a tendency for similarity in the constructs and measures. Furthermore, investigators in these areas increasingly recognize the importance of data comparability, interoperability, and integration across multiple studies (Curran and Hussong, 2009), particularly in the area of gene-environment interactions (Bennett et al, 2011; Bierut, 2011; Cornelis et al, 2010; Duncan and Keller, 2011), a research portfolio that is largely housed within the epidemiology domain.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, it is reassuring that GWAS meta-analyses have proven to be successful at addressing for other complex phenotypes, including behavioral measures (67,68). Furthermore, simulation studies suggest that, even with exposure misclassification, very large studies can succeed at identifying susceptibility loci (69). Importantly, if even a subset of genetic influences is common across each alcohol metric, then a meta-analysis should be able to identify genes contributing to this shared genetic propensity, given a large enough data set.…”
Section: The Future Of Gwas Meta-analyses Of Alcohol Consumptionmentioning
confidence: 99%
“…Thus, depending on the goals of a study, measures of alcohol consumption can be collected by using food-frequency questionnaires, from medical charts, via self-report in case-control studies of health-related outcomes, and from interviews in studies for addiction and other psychiatric disorders. To illustrate this remarkable variation in the assessment of alcohol consumption, representative alcohol-consumption measures from individual studies of the GENEVA Consortium are shown in Table 1 (46,47).…”
Section: Why Measurement Heterogeneity Occursmentioning
confidence: 99%